Psychological Emotion and Behavior Analysis in Music Teaching Based on the Attention, Relevance, Confidence, and Satisfaction Motivation Model - Li, Dong (Frontiers in Psychology, 2022)
ARCS motivation model is a systematic and easy-to-operate motivation theory. Its applicability and effectiveness have been verified in education at home and abroad. Based on the traditional ARCS motivation model, the ARCS motivation model is optimized to make the model more suitable for the coding system of music classroom teaching. The case analysis method is used to select 14 high-quality music lessons as the research object. The text conversion, coding, and statistical analysis are carried out on the class videos of high-quality lessons. Data analysis is used to analyze students' psychological emotions and behavioral motivation incentive strategies in each ARCS motivation model combined with specific high-quality lesson case fragments. Finally, this study summarizes the ways and methods of using motivational strategies in the exploratory teaching of music quality classes, which provides theoretical support for the practice of music teaching.